Effect of dietary citric acid and microbial phytase on the growth performance of broiler chickens - Listya Purnamasari; Michael S. Paras; Joseph F. dela Cruz (Fakultas Peternakan, Universitas Padjadjaran, 2022)
Feed additives are one of the most essential parts of broiler production. Feed additives such as citric acid and microbial phytase are usually used separately despite the theory that they can work together. In this study, 320 broiler birds were reared and then fed four different treatments. 10 birds were reared per pen and there were 8 replications per treatment. The birds were reared using normal broiler management and health management protocols. The growth parameters and mortalities were recorded after each growth period. Production cost and the market price during the duration of the experiment were used to assess profitability. Out of all the treatments, the combination of the citric acid and microbial phytase gave the highest body weight, weight gain, second-lowest feed intake, best feed conversion ratio, and the highest profitability. Results indicated that there is a synergistic interaction with the combination of 3% citric acid and 500 U/kg microbial phytases. The concurrent supplementation produced a significant increase in the growth parameters and profitability.